Politics. - Eaton, George (New Statesman, 2016)
The article focuses on how the European Referendum will affect the standing of the British Labour Party under the leadership of Jeremy Corbyn. Topics discussed include the vote of no confidence expressed by Labour parliamentarians against Corbyn and the resulting calls for his resignation. Opposition to Corbyn's soft left program and the challenge for the Labour leader to uphold party unity are mentioned.